Total Mikroba dan Masa Simpan Tahu dengan Perendaman Ekstrak Kunyit - Ravi Masitah; Agus Wijanarka; Devillya Puspita Dewi (Pusat Riset dan Inovasi Nasional, 2025)
Background: Tofu is a food which has high protein content but it is quickly damaged, so natural ingredients are needed to extend the shelf life and minimize microbial growth. Objective: The study aims to analyze the total microbial and tofu storage period by immersing turmeric extract. The research methods were in the form of survey in tofu factory, purchasing tofu, making turmeric extract, tofu storage, microbial total test with Total Plate Count and the tofu storage period were observed starting from the third, fourth and fifth days every 24 hours. The parameters observed were total microbes and shelf life of tofu. The study used a simple randomized design (RAS) with 4 treatments, 2 experimental units and 2 repetitions. The data obtained were analyzed descriptively and presented in tabular form and carried out documentation. Results: The results showed that tofu with the highest concentration of turmeric extract which was 15%, had a total microbial of at least 7.2 x 1010 CFU / gram and the longest shelf life was three days of storage. Conclusion: The conclusions are the higher concentration of turmeric extract is given; the raising level of total microbes will be lowest and make the shelf life of tofu longer.